From Policy to Practice: Institutional Pathways Toward Environmental Justice in the Global South - Azzahra, Aisha (Yayasan Sinergi Kawula Muda, 2024)
Environmental justice has become an increasingly urgent issue in developing countries, where legal reforms often fail to reflect equitable outcomes on the ground. This study aims to explore the interplay between institutional capacity, public policy, and environmental inequality, emphasizing the need for inclusive governance frameworks. Employing a narrative review methodology, the study systematically synthesizes empirical literature drawn from databases such as Scopus, Web of Science, and Google Scholar. Keywords and Boolean operators were applied to identify studies focusing on environmental justice, law, and governance in developing countries, with inclusion criteria targeting empirical and comparative studies. Findings reveal that although legislative reforms have made significant progress in integrating principles of environmental justice, weak institutions and fragmented policy implementation continue to hinder equitable outcomes. Public participation mechanisms and community-based advocacy play a crucial role in bridging governance gaps. Furthermore, comparative analysis with countries in the Global North highlights the importance of decentralization, legal accountability, and participatory oversight in achieving meaningful reform. The results underscore the urgent need for systemic interventions that go beyond legislative reform, including the strengthening of institutions, adoption of independent audit systems, and increased civic engagement. This study recommends multi-dimensional policy models that combine legal, technological, and participatory tools to build resilient environmental justice systems. These insights provide actionable pathways for governments, researchers, and civil society to design more equitable and sustainable environmental governance in the Global South.